Alkaline rocks of the northern part of Birnin Gwari schist belts, northwestern Nigeria: provenance and evolution - O. Oluyede, Kehinde (International Journal of Advanced Geosciences, 2021)
Rocks of the northern part of Birnin Gwari schist belt is underlain predominantly by (i) banded gneiss of dioritic and granodioritic composition and granitic gneisses; (ii) biotite-staurolite quartz schist; and (iii) syn-tectonic biotite hornblende (quartzolite - BHG) granite, biotite granite (BG), and biotite-muscovite granite (BMG). Banded gneiss rocks are of hybrid sedimentaryâ€“igneous protoliths; their pelitic and mafic protoliths were derived essentially from a quartz-diorite, granodiorite and granite-quartz monzonite source. Metasediments are enriched in SiO2 (63.03 to 65.13 wt %), with moderately elevated Al2O3 (15.4 â€“ 15.16 wt %) values and depleted in Ba, V, W, La, Nb, Nd, Rb, Th and Zr trace elements; inherited from shale-greywacke sedimentary protoliths. Cogenetic syn-tectonic granites display similar trace elements and REE patterns, with diverse trends such as â€œnormalâ€, â€œanomalousâ€ and â€œstrongly differentiatedâ€ and characterized by LILE enrichment, high LREE fractionation factor (La/Yb of 6.74 to 45.14) with weak to moderate negative Eu (Eu/Eu* = 0.38 to 0.62) and strong negative Nb, P and Ti anomalies. The belt consists of rocks with alkaline affinity and evolved as back arc behind subducted Pan-African plate due effect of compressional forces and differentiation of quartz diorite, granodioritic and granite-quartz monzonite magma and partial melting of crustal components inherited from shale-greywacke sedimentary protoliths in volcanic arc and post collisional settings. The precursor of these rocks originated from basalt of depleted mantle that differentiated progressively to the granite.Â Â Â